Determinants of international remittance inflows in middle-income countries in Asia and the Pacific - Naoyuki Yoshino; Farhad Taghizadeh-Hesary; Miyu Otsuka (Asian Development Bank Institute (ADBI), 2019)
The middle-income trap is a serious problem in developing Asia and Pacific economies. Middle-income trap is the situation in which a country's growth slows after reaching middle-income levels and the transition to high-income levels becomes unattainable. International remittances of immigrants to their country of origin is one of the most important elements contributing to the development of middle-income countries. This paper by using data set consists of 12 Asia and Pacific middle-income countries - most of which are well-known migrant-sending countries - and by employing a panel data analysis technique, tried to find the determinants of international remittance. Results show that per capita gross domestic product growth in origin countries and wage growth rate in destination countries are positively correlated with remittance inflows in middle-income countries, respectively. On the other hand, net foreign direct investment (FDI) inflows are negatively correlated with remittance inflows. This can be interpreted as the paradigm shift of acquiring foreign capital in middle-income countries from remittance in earlier stages of development to more FDI when the country prepares the requirements for absorbing the foreign capital with an economic growth. Moreover, real effective exchange rate, the level of education, trade openness, and political stability are positively associated with remittance inflows.
Keywords: I31; I32; I38; 330; remittance; middle-income trap; poverty; developing Asia and the Pacific